Teachers’ Professional Vision: Teachers’ Gaze During the Act of Teaching and After the Event - Minarikova, Eva; Smidekova, Zuzana; Janik, Miroslav; Holmqvist, Kenneth (Frontiers in Education, 2021)
To date most of our knowledge on professional vision has relied on verbal data or questionnaires that used classroom videos as prompts. This has been used to tell us about a teacher’s professional vision. Recently however, new studies explore professional vision during the act of teaching through the use of mobile eye-tracking. This novel approach poses the question: how do these two “professional visions” differ? Visual attention represented by gaze was used as a proxy to studying professional vision (specifically its noticing component). To achieve this, eye-tracking as data collection method was used. We worked with 3 teachers and employed eye-tracking glasses to record teacher eye movements during teaching (4 lessons per teacher). After each lesson, we selected short clips from the lesson recorded by a static camera aimed at pupils and showed them to the same teacher (i.e., providing a similar setting as traditional studies on professional vision) whilst recording eye movements and gaze behavior data through a screen-based eye-tracker. The two modes differ and due to these differences, comparison is difficult. However, by overlaying them and describing them in detail we want to highlight the exact variance observed. A comparison between IN vs ON condition in terms of dwell time on the same students in either condition was made using both quantitative (correlation) and qualitative (timeline comparison) methods. The findings suggest that the greatest differences in attention given to individual pupils occurs when a pupil who was interacted with during the situation is missing from the view in the video recording. Even though individual differences are present in the patterns of gaze in IN and ON mode, the teachers in our sample consistently monitored more pupils more often in the ON mode than in the IN mode. On the other hand, IN mode was mostly characterized by focused gaze on the pupil that the teacher interacted with in the moment with few side glances. The results aim to open a discussion about our understanding of professional vision in different contexts and about how current research may need to expand its outlook.